Value capture and distribution in second-hand clothing trade: The role of charity discourses, commercial strategies and economic and political contexts - Linda Lampel (Südwind-Verlag, 2020)
The Master thesis of Ms. Linda Lampel with the title "Value Capture and Distribution in Second-Hand Clothing Trade. The Role of Charity Discourses, Commercial Strategies and Economic and Political Contexts" analyzes second-hand clothing trade based on a global production network (GPN) perspective. Given the large-scale geographic reorganization of production at the global level since the 1970s, which also had important effects on the economies of the Global South, GPN analysis has become a topical field of inquiry in development studies. An innovative contribution of Ms. Lampel thesis is the linking of the GPN framework to theoretical approaches on discarded goods, enabling the analysis to assess how value is captured and distributed in global second-hand clothing GPNs. The analysis particularly focuses on the role of actors in Austria, Germany and Morocco and highlights the different positions of actors in these countries in second-hand clothing GPN. In doing so, the thesis reveals the problematic links between fast fashion dynamics and environmental concerns as well as the blurred line between charitable and commercial actors in the trade with used cloths.Given the eminent role of economic, social and environmental sustainability issues in European and Austrian Development Cooperation, the novel methodological approach applied in this study is of particular relevance for the current discussions on increasing the sustainability in the textile and apparel/second-hand clothing industry.
Keywords: 330